Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Open Ended Problem untuk Meningkatkan Keterampilan Proses Sains - I Gusti Ayu Agung Mas Purohita; I Wayan Subagia; Ketut Suma (Wahana Matematika dan Sains: Jurnal Matematika, Sains, dan Pembelajarannya, 2023)
This research aims to develop open ended problem worksheet products that adapt pre-existing worksheets. Then the LKPD was tested to find out the validity, practicality, and effectiveness of improving junior high school students' science process skills. This type of research is development research by adapting the Borg and Gall development model. Data in this study were collected using validation questionnaires, practicality questionnaires and observation of students' science process skills. The results of this study show: (1) the gregory validity coefficient for material validity KVG is 0.95 with very valid qualifications, for media validity results a score is 96 with very valid qualifications and language validity results obtain a score is 96 with very valid qualifications, (2) the results of the practicality test show that LKPD is very practical from teacher practitioners is 85.50. (3) The results of the effectiveness test show that the improvement of students' science process skills is in the good category. Based on the research results, it can be concluded that (1) LKPD has characteristics according to open ended problems, (2) LKPD has obtained valid assessments, (3) LKPD has obtained practical assessments, and (4) LKPD is effective in improving participants' science process skills educate. Keywords: student worksheets, open ended problem, science process skills.